Application of polyurethane in the production of shoe soles - Rajić, Ivona (Array, 2021)
Good footwear should be comfortable, long-lasting and fit for purpose, polyurethanes allow designers to meet all of these objectives. Polyurethanes are used in the footwear industry to make insoles and shoe soles.There are two types of PU soles a polyether and polyester based PU sole. Polyether based PU soles have a high resistance against hydrolysis and low oil resistance while polyester based PU soles have a low resistance against hydrolysis and high oil resistance. In this work thermal and mechanical properties of PU elastomers with polyether and polyester polols with different hard segment content were investigated. Differential scanning calorimetry (DSC) indicated partial crystalinity structure of the PU elastomers. PU elastomers based on polyether type polyol show the higher degree of crystalization. Based on DMAresults , Tgvalues of the PU increases and broadened with increasing hard segment content in the PU elastomers based on polyester polyol, due to the interaction between the urethane groups and the ester carbonyl groups. Mechanical studies indicated that the tensile strength of PU elastomers increased with hard segment.